The experience of fathers with the kangaroo mother care method: an integrative review - Thaís Rosental Gabriel Lopes; Jovanka Bittencourt Leite de Carvalho; Tássia Regine Morais Alves; Anderson Brito de Medeiros; Sylvia Silva de Oliveira; Francisco Arnoldo Nunes de Miranda (Universidade Federal do Ceará, 2019)
Objective: to understand the experience of fathers with the kangaroo mother care method. Methods: an integrative literature review in the following databases: Scientific Electronic Library Online, Medical Literature Analysis and Retrieval System Online, Latin American and Caribbean Health Sciences, Web of Science, Current Nursing and Allied Health Literature. Results: a total of 732 articles were obtained and seven were selected. It was identified that fathers experienced the kangaroo method with fulfillment and pleasure. They presented difficulties, fears and insecurities that may be associated with the functioning and life support devices used to ensure the survival of premature infants, related to the distancing between father and newborn. Conclusion: the father is currently more participative and aware of his role in the family environment and in the care inherent to the premature child. However, despite feeling unprepared, fathers are proud and hopeful with the clinical evolution when experiencing the kangaroo method.